P3.275 Neisseria Gonorrhoeae: Situation of Antibiotic Resistance in Germany. (13th July 2013) - Buder, S; Kohl, P K
Abstract : Background: The dramatic development of antimicrobial resistance in Neisseria gonorrhoeae is a serious problem for treatment and control of gonorrhoea. Numerous formerly effective therapeutic agents are no longer appropriable. High level penicillin resistance and quinolone resistance disseminated globally. The third generation cephalosporins are amongst the last agents to remain effective. Reduced susceptibility to these cephalosporins is increasingly common. Currently the emergence of cephalosporine resistance in gonococci can be observed. There is a grave concern that multidrug resistant Neisseria gonorrhoeae strains will develop (MDR-NG). Methods: Non-selected collection of Neisseria gonorrhoeae isolates from all regions of Germany. It is the aim of this surveillance to monitor the antimicrobial resistance to a range of therapeutically relevant antimicrobials as third generation cephalosporins (cefixime, ceftriaxone), azithromycin, gentamicin, spectinomycin, ciprofloxacin and penicillin. Results: We report current results from the 2011/12 antimicrobial resistance (AMR) surveillance in Germany. More than 10% of the isolates displayed decreased susceptibility to cephalosporins, mostly to cefixime. Nearly 5% of all isolates showed a decreased susceptibility to both cephalosporins. All of these isolates also displayed resistance to ciprofloxacin. Conclusion: Cefixime is no longer recommended as first line therapy agent due to a high number of isolates with decreased susceptibility. Ceftriaxone is an appropriate treatment for gonorrhoea, but a drift to decreased susceptibility can be observed. Azithromycin remains still effective. Rates of ciprofloxacin and penicillin resistance are high across Germany.